2022
DOI: 10.1039/d2ta02257e
|View full text |Cite
|
Sign up to set email alerts
|

Understanding (photo)electrocatalysis for the conversion of methane to valuable chemicals through partial oxidation processes

Abstract: Methane (CH4) with sp3 hybridization is known as a main constituent of natural gas, which has been utilized as a fuel and a hydrogen reservoir for power plant and transportation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 117 publications
1
13
0
Order By: Relevance
“…The reaction system requires a power source, cathode, and anode separated by ion‐exchange electrolytes and membranes. [ 27 ] Different reviews have been recently reported, focusing on the direct and indirect electrochemical CH 4 activation, [ 410 , 411 ] electrocatalyst structures, [ 28 ] electrolytes, [ 411 ] mechanistic understanding, reaction engineering, [ 412 ] and theoretical modeling. [ 413 ] One of the primary benefits of electrocatalysis is the variety of ways to activate CH 4 at room temperature by avoiding the use of strong oxidants such as H 2 O 2 , which has the potential to reduce operating costs compared to thermal catalytic systems.…”
Section: Catalytic Activation Of Methane At Relatively Low Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…The reaction system requires a power source, cathode, and anode separated by ion‐exchange electrolytes and membranes. [ 27 ] Different reviews have been recently reported, focusing on the direct and indirect electrochemical CH 4 activation, [ 410 , 411 ] electrocatalyst structures, [ 28 ] electrolytes, [ 411 ] mechanistic understanding, reaction engineering, [ 412 ] and theoretical modeling. [ 413 ] One of the primary benefits of electrocatalysis is the variety of ways to activate CH 4 at room temperature by avoiding the use of strong oxidants such as H 2 O 2 , which has the potential to reduce operating costs compared to thermal catalytic systems.…”
Section: Catalytic Activation Of Methane At Relatively Low Temperaturementioning
confidence: 99%
“…Therefore, it is suggested to focus on electrocatalysts with low Gibbs free energy for CH 4 activation and high Gibbs free energy for water oxidation, such as V 2 O 5 , TiO 2 , PtO 2 , and RhO 2 . [ 27 , 417 , 418 ] Moreover, substantial issues exist in separating products from electrolytes. [ 28 ] Furthermore, there is still a problem associated with poor mass transfer and low solubility of CH 4 for membrane electrode assemblies.…”
Section: Catalytic Activation Of Methane At Relatively Low Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Therefore, it is highly desirable to explore alternative approaches to achieve the conversion of CH 4 under mild conditions. In this regard, photocatalytic CH 4 oxidation is considered to be a promising strategy to achieve the cost-effective utilization of CH 4 , [10][11][12][13] by employing inexhaustible and clean solar energy to generate hot electron-hole pairs over catalysts to directly or indirectly activate the C-H bonds of CH 4 , which has attracted ever-increasing attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] In addition to burning as an energy vector (generally be considered as a potential alternative to oil), methane as a greenhouse gas with an effect 30 times more signicant than CO 2 can be used as a chemical feedstock for value-added transformations. [30][31][32][33][34][35][36] Catalytic chemical activation of both stable small molecules as a promising way to overcome the obstacle has attracted ever-increasing attention. However, due to the ultra-high stability of the C]O and C-H bonds, the catalytic conversion of both CO 2 and methane is energy-intensive and occurs typically at high temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%